2021
DOI: 10.17241/smr.2021.00948
|View full text |Cite
|
Sign up to set email alerts
|

Epiglottic Collapse in Obstructive Sleep Apnea

Abstract: Along with the development of diagnostic techniques, many studies have been conducted to find the anatomical causes of obstructive sleep apnea (OSA). The velum, oropharynx, tongue base, and epiglottis have been widely considered to be the common obstruction sites. However, the role of the epiglottis in sleep apnea is poorly understood compared to the other anatomical sites. The epiglottis causes OSA either alone or simultaneously with other obstruction sites. We have here reviewed the epidemiology, pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Kim et al confirmed this assertion by publishing an article with an OSA patient with worsening epiglottic collapse during CPAP application in a video presentation [45]. In case of residual obstruction after CPAP, an upper airway reassessment should be performed to determine the presence and type of epiglottic collapse [46], as these patients require different management.…”
Section: Discussionmentioning
confidence: 95%
“…Kim et al confirmed this assertion by publishing an article with an OSA patient with worsening epiglottic collapse during CPAP application in a video presentation [45]. In case of residual obstruction after CPAP, an upper airway reassessment should be performed to determine the presence and type of epiglottic collapse [46], as these patients require different management.…”
Section: Discussionmentioning
confidence: 95%
“…If there is a long glosso-epiglottic fold and therefore a lot more space between the base of the tongue and the epiglottis, then one would more likely encounter the trap-door phenomenon. Conversely, if the valecullae are extremely narrow with a short gloss-epiglottic fold and a shorter but tighter glosso-epiglottic fold, then the pattern of collapse would be different [ 28 ]. Additionally, an ary-epiglottis fold pattern of collapse may also be observed, which is similar to laryngomalacia in pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have classified EC as apEC and latEC with partial or complete types. The most common type, complete apEC, has an incidence rate of 16.8% to 65.4%; latEC is the least common type 17 . We screened 352 OSA patients, and the final analysis included 40 patients with apEC (35 complete and 5 partial types) and 14 patients with latEC (11 complete and 3 partial types).…”
Section: Discussionmentioning
confidence: 99%